PENGARUH SISTEM RECRUITMENT KEMAMPUAN KERJA DAN PELATIHAN PEGAWAI TERHADAP KINERJA PEGAWAI DI BADAN PENDAPATAN DAERAH KABUPATEN DELI SERDANG - Ade Irma; Mhd. Dani Habra (Universitas Dharmawangsa, 2022)
The purpose of this study is to see how the recruitment system, job ability, and employee training affect employee performance at the Deli Serdang Regency's Regional Revenue Agency. The sample size in this study was 53 employees, and the sampling method was simple random sampling using the Slovin algorithm. Interviews and the distribution of study questionnaires to personnel of the Regional Revenue Agency of Deli Serdang Regency provided the research data. Multiple linear regression analysis was utilized to analyze the data. The findings of this study show that the recruitment system has a small but beneficial impact on employee performance. Then, work ability has a favorable and significant effect on employee performance, and finally, employee training has a positive but negligible effect on the performance of the Deli Serdang Regency's Regional Revenue Agency.